Preparing future health professionals via reflective pedagogy: a qualitative instrumental case study. Issue 5 (3rd September 2019) - Burnett, Audrey J.; Akerson, Emily
ABSTRACT: Simulation activities prepare students for situations and populations that they may encounter as health care professionals working in teams. The current project aimed to interpret students' reflections regarding a simulation that exposed students to the difficulties associated with poverty that many of their patients experience. Students were asked to reflect on their learning regarding ethical decision-making and their future role as a health professional. As part of a course requirement over the course of two semesters, a total of 106 undergraduate health sciences majors were randomly assigned to a unique family unit for a three-hour hands-on simulation in collaboration with other majors and local professionals/agencies. Students were required to navigate the various community agencies while also providing basic needs for their respective families. Prompts were provided for students' written reflections following the simulation. NVIVO 12 ® revealed several major themes that were most prominent in students' written reflections, with notable student quotes included. The impact of the simulation on students' evaluation of structural/systemic and personal problems within their assigned family units was demonstrated via the major themes. Students displayed advanced critical thinking and application skills via their written reflections, which exemplified the effectiveness of the simulation as an impactful learning opportunity.